One step excision combined with unilateral transforaminal intervertebral fusion via minimally invasive technique in the surgical treatment of spinal dumbbell-shaped tumors: A retrospective study with a minimum of 5 years’ follow-up - Pan, Jianfeng; Gu, Yutong; Zhang, Feng (Frontiers in Surgery, 2022)
Introduction Spinal dumbbell-shaped tumors are rare, usually benign tumors with intraspinal and paravertebral components connected through intervertebral foramen. Complete excision is often performed through traditional open surgery (TOS). The efficacy and long-term outcomes of minimally invasive surgery (MIS) have not been reported to date in resection of dumbbell-shaped spinal tumors. Purpose The purpose was to evaluate the efficacy and long-term outcomes of minimally invasive resection combined with unilateral transforaminal intervertebral fusion (TIF) through comparing with TOS in the treatment of spinal dumbbell-shaped tumors. Methods Fifteen patients underwent MIS and 18 patients underwent TOS. Thoracic dumbbell-shaped tumors were directly exposed after removal of costotransverse joints, adjacent rib components, unilateral hemilamina, and facet joints. Lumbar dumbbell-shaped tumors were completely exposed after removal of transverse processes, unilateral hemilamina, and facet joints. Whether for minimally invasive resection or traditional open removal, dumbbell-shaped tumors were completely excised and unilateral TIF was performed to guarantee spinal stability. All patients were followed up for 5 years at least. Results The mean length of surgical incision for two groups was 3.47 ± 0.37 vs. 6.49 ± 0.39 cm (p < 0.05). The average duration of the operation was 131.67 ± 26.90 vs. 144.17 ± 23.59 min (p > 0.05). The mean blood loss was 172.00 ± 48.79 vs. 285.83 ± 99.31 ml (p < 0.05). No blood transfusions were required in the two groups. The median length of hospitalization was 6 vs. 10 days (range: 5–8 vs. 7–14 days). The patients of two groups were monitored for an average of 65.93 ± 3.88 vs. 65.78 ± 3.56 months. At 5-year follow-up, all patients presented with normal neurological function (American Spinal Injury Association scale E). The Oswestry Disability Index in the MIS group decreased significantly more than the TOS group. No spondylolisthesis or spinal instability were found in the follow-up period. There was no recurrence of any spinal tumor 5 years after surgery. Conclusions Spinal dumbbell-shaped tumors can be safely and effectively treated with minimally invasive resection combined with unilateral TIF. Compared with TOS, MIS offers a reduced length of surgical incision, blood loss, hospital stay, and postoperative pain. This surgical protocol might provide an alternative for the treatment of spinal dumbbell-shaped tumors.